Pendampingan Pengembangan E-LKPD Menggunakan Liveworksheet pada Guru Sekolah Dasar - Zukhrufurrohmah Zukhrufurrohmah; Fahdian Rahmandani; Adi Slamet Kusumawardana; Ririt Rahma Wati (Educivilia: Jurnal Pengabdian pada Masyarakat, 2025)
The main problem faced by the partner schools is the suboptimal implementation of online learning due to the lack of adequate learning media that support distance learning. One of the major challenges is the absence of interactive Student Worksheets (LKPD) that can be effectively utilized in online learning. Therefore, the Community Service Team provides a solution through a training and mentoring program aimed at developing e-LKPD using the Liveworksheet platform. With this e-LKPD, teachers can deliver more interactive and engaging learning materials aligned with the expected competency achievements in the curriculum. This program is carried out in three main stages: the training stage, which provides fundamental understanding; the mentoring and development stage, which assists teachers in hands-on practice; and the evaluation stage, which assesses the effectiveness of e-LKPD implementation in the learning process. The evaluation is conducted through interviews with teachers before and after the training, as well as observations during the learning activities. The results indicate an improvement in teachers' understanding of e-LKPD development based on learning indicators. Teachers are also able to create engaging student activities by utilizing various interactive features available on the Liveworksheet platform. This contributes to enhancing the quality of online learning, making it more effective and innovative.